Step-by-step explanation:
x -2 -1 2 7
y -6 -6 -2 3
All y are in under root
We use the formula a^2 - b^2 = ( a - b )( a + b );
We have a = 5m - 2 and b = 3m - 4;
<span>(5m-2)^2-(3m-4)^2 = (5m - 2 -3m + 4) x (5m-2 + 3m - 4) = (2m + 2)(8m - 6) = 2(m +1) x 2(4m - 3) = 4(m+1)(4m-3);
</span>
Answer:
=125
Step-by-step explanation:
5−7)(512)(5−2)
=
1
78125
(512)(5−2)
=
1
78125
(512)(5−2)
=(
1
78125
(244140625))(5−2)
=3125(5−2)
=3125(
1
25
)
=125
Answer:
a=64° alternating angles
b=40° corresponding angles
Answer:
The volume is <u>1539.38</u>
Step-by-step explanation: